An Empirical Study on the Closed-end Funds Puzzle: The Case in China's Mutual Funds Market - Yang, Liu (2007)
It is considered as an anomaly that closed-end funds are often traded at discounts by the efficient market hypothesis (EMH) theory. This puzzle includes four pieces which together capture the life cycle of a closed-end fund. There are many empirical studies related to this field, but the theories have not reached a common until now and either on the base of rational analysis or irrational interpretation cannot fully explain the closed-end fund puzzle. This paper aims to explore the phenomenon of discounts on closed-end funds. Closed-end fund puzzle in China could be explained by several theories. Through the empirical study on Chinese fund market, it indicates that asset liquidity hypothesis seems to well interpret the closed-end fund puzzle in China. This phenomenon is related to the background and system of Chinese stock market. Since the notion of long term investment has not been accepted by most investors, the market liquidity tends to attract more investors' attention. In the examination of investor sentiment theory, which is proved to be key factor of asset pricing,results show that the correlation between returns on fund portfolio and fund discounts is not as obvious as it was expected. The robustness of this conclusion,however, is difficult to test, so the returns on fund portfolios do not do a good jobin measuring investor sentiment.